Education Of The Interpretation Of The Qur'an In The Period Of The Prophet Muhammad Saw - Ilma Amalia; Muhammad Abdul Kholiq; Ade Jamarudin (al-Afkar, Journal For Islamic Studies, 2023)
Education is an attempt to change something for the better or directed. With education, knowledge that we don't have turns into knowledge that we know, therefore education is the starting point for human life and civilization. Alqur’an is the first educational guide in the life of mankind, especially Muslims. Therefore, knowledge of the contents of the Qur'an is very important for Muslims to have. Through education, we will know how and what meaning Allah wants to give or order to us as His people. Education and teaching of the Alqur’an had started since the early days of the revelation of the Alqur’an, namely during the time of the Prophet Muhammad. The various interpretations of the Alqur’an that have come down to us are clear evidence that Rasulullah SAW is the best teacher of Alqur’an interpretation. This paper contains about how the education and development of the interpretation of the Qur'an in the era of Rasulullah SAW. The method used by the author is a qualitative method with a literature study approach. The aims and results of this study are: education during the time of Rasulullah SAW, Tafsir Alqur’an in the era of Rasulullah SAW and Rasulullah SAW as interpreter of Alqur’an.